Exploring Linguistic Strategies in Romanian Clickbait Headlines: Communication Tactics in Online Media - Marcela Alina FĂRCAȘIU; Vasile GHERHEȘ (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
This study investigates the communication tactics embedded in clickbait headlines found in Romanian online media, by linguistically analysing a corpus of 80 headlines sourced from the Libertatea newspaper. It identifies key strategies such as the use of questions, numbers and dramatic language, all crafted to provoke curiosity and evoke emotional reactions from readers. By examining these linguistic techniques, the paper sheds light on the manipulative structures that drive digital engagement through clickbait in Romania. Furthermore, the findings provide a foundation for developing more advanced algorithms for clickbait detection and emphasise the critical need to understand how these strategies affect the credibility and quality of online journalism.